Crossover Clinical Trial of Tablets Containing Sodium Tripolyphosphate on Dental Stain Formation - Porciani, Pier Francesco; Grandini, Simone (The Journal of clinical dentistry, 2018)
The purpose of this clinical investigation was to evaluate the effectiveness of sugar-free tablets containing sodium tripolyphosphate 2% or sodium tripolyphosphate 0.65%, compared to a no-tablet control in preventing the formation of extrinsic stains over a 12- week period of regular unsupervised use preserving daily oral hygiene with dentifrice and usual tooth brushing. This was a single-center, examiner-blind, randomized, 12-week crossover clinical trial. Sixty-six adult participants were enrolled in the study and were submitted to a professional cleaning to have a stain-free baseline. They either consumed two sugar-free tablets four times per day or not for 12 weeks. At the crossover, all procedures were repeated and subjects were assigned to another group. Extrinsic stain was measured at each 12-week period by the Modified Lobene Stain Index (MLSI). After the three legs of 12 weeks, 60 subjects completed the trial, their MLSI stain scores showed a significant 35.5% reduction (p < 0.001) in new stain formation for those using the sodium tripolyphosphate 2% tablets, and a significant 23.3% reduction (p < 0.001) in new stain formation for those using the sodium tripolyphosphate 0.65% tablets versus the control group. This clinical study showed that regular use of sugar-free tablets added with sodium tripolyphosphate 2% or 0.65% can reduce stain formation on the anterior teeth respectively by 35.5% (p < 0.001) or 23.3% (p < 0.001), both on facial and lingual/palatal surfaces.